How symptoms of simple acute infections affect the SSS-8 and SSD-12 as screening instruments for somatic symptom disorder in the primary care setting - Zhang, Ying; Baumeister, David; Spanidis, Mona; Engel, Felicitas; Berens, Sabrina; Gauss, Annika; Eich, Wolfgang; Tesarz, Jonas (Frontiers in Psychiatry, 2023)
Objective: Somatic symptom disorder (SSD) is one of the most common reasons for consultations in primary care, in addition to simple acute infections. Questionnaire-based screening instruments to identify patients at high risk of SSD are thus of great clinical relevance. Although screening instruments are frequently used, it is currently unclear to what extent they are influenced by the concurrent presence of simple acute infections. Therefore, this study aimed to investigate how symptoms of simple acute infections affect the two established questionnaires as screening instruments for somatic symptom disorder in the primary care setting. Methods: In our cross-sectional, multicenter design, a total of 1,000 patients in primary care practices were screened using the two most established SSD screening questionnaires, the 8-item Somatic Symptom Scale (SSS-8) and the 12-item Somatic Symptom Disorder - B Criteria Scale (SSD-12), followed by clinical assessment by the primary care physician. Results: A total of 140 patients with a simple acute infection (acute infection group, AIG) and 219 patients with chronic somatic symptoms (somatic symptom group, SSG) were included. The patients in the SSG showed higher total SSS-8 and SSD-12 scores than the patients in the AIG; however, the SSS-8 was more susceptible to changes triggered by symptoms of a simple acute infection than the SSD-12. Conclusion: These results suggest that the SSD-12 is less susceptible to symptoms of a simple acute infection. Its total score and corresponding cutoff value provide a more specific and thus less susceptible screening tool for identifying SSD in primary care.